Reviews of Books (International review of mission, 1962)
THE CHURCH IN AN URBAN SETTING: CITIES AND CHURCHES: READING ON THE URBAN CHURCH. Edited by Robert Lee. TECHNICAL AID AND SOCIAL CHANGE: TRADITIONAL CULTURES AND THE IMPACT OF TECHNOLOGICAL CHANGE. By George M. Foster. MARRIAGE IN AFRICA: LE MARIAGE EN AFRIQUE NOIRE. By Jacques Binet. RETENTION OF IDENTITY: THE KONKOMBA OF NORTHERN GHANA. By David Tait. PHILANTHROPIC ADVENTURE: A HISTORY OF SIERRA LEONE. By Christopher fyfe. INDIAN CULTURES IN BRITISH COLUMBIA: THE STRUGGLE FOR SURVIVAL: INDIAN CULTURES AND THE PROTESTANT ETHIC IN BRITISH COLUMBIA. By F. E. LaViolette. RECONSTRUCTION THROUGH LEISURE: EDUCATION FOR LEISURE. By S. R. Ranganathan. FRESHNESS OF VISION: JESUS CHRIST: An illustrated Life of Christ, with text from the New English Bible. Introduction By C. A. Rijk. THE NESTORIAN CHURCH AND WESTERN INFLUENCE: THE NESTORIANS AND THEIR MUSLIM NEIGHBORS: A STUDY OF WESTERN INFLUENCE ON THEIR RELATIONS. By John Joseph. FROM A MOSQUE TO A UNIVERSITY: AL-AZHAR: A MILLENNIUM OF MUSLIM LEARNING. By Bayard Dodge.